Investigation or the effects of prostaglandin f2α, furosemid and indomethacin on sperm characteristics in rams - İbrahim Pirinçci; İzzet Karahan; Tanzer Bozkurt; Osman Güler (Eurasian Journal of Veterinary Sciences)
This investigation was made to establish the effects of PGF2α, furosemid, indomethacin and the combinations of these drugs on the sperm volume, viscosity, mass activity, motility, density and abnormal spermatozoa rate in rams. In the study, 70 Akkaraman rams, approximately 2 years old were used. PGF2α (0.1, 0.2 and 0.3 mg/ kg), furosemid (2.0, 4.0 and 6.0 mg/kg). indomethacin (3.0, 6.0 and 9,0 mg/kg) and the combinations of these drugs were intramuscularly given the animals In one dose and in doses following on each other's four days. The sperm samples were collected after administrations. Sperm characteristics were determined in the samples. The sperm volume. motility and density were established to decrease but the increase in abnormal sperm rate in the sperm samples in the rams given in one dose and in doses following on each other's four days PGF2α and furosemid. However, sperm characteristics weren't altered in the rams given indomethacin. In conclusion, it was decided that prostaglandins and drugs effecting prostaglandin synthesis could alter sperm production and sperm characteristics.